Balaenoptera acutorostrata Lacepede 1804 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
1. Common Minke Whale Balaenoptera acutorostrata French: Petit Rorqual / German: Nordlicher Zwergwal / Spanish: Rorcual aliblanco Other common names: Lesser Rorqual, Little Piked Whale, Sharp-headed Finner Whale: North Atlantic Minke Whale (acutorostrata); North Pacific Minke Whale (scammoni) Taxonomy. Balaenoptera acutorostrata Lacépede, 1804, France, “pris aux environs de la rade de Cherbourg,” Manche. Although distinct populations of Minke whales are known to occur in different ocean basins, only a single, cosmopolitan species was officially recognized until the 1990s. A taxonomic review in 1998 concluded that the population of larger-bodied B. acutorostrata in the high latitude regions of the Southern Ocean should be separated based on genetic and morphological grounds and assigned to a different species, B. bonaerensis. This species is distinctly larger than B. acutorostrata and generally sympatric with an unnamed form in the Southern Hemisphere, generally called the dwarf Minke whale. Two subspecies recognized. Subspecies and Distribution. B.a.acutorostrataLacépede,1804—NAtlanticOcean. B. a. scammoni Demére, 1986 — N Pacific Ocean. An unnamed form is found in the Southern Hemisphere. Descriptive notes. Total length 650-880 cm; weight 2000-2700 kg. Adult female Common Minke Whales are slightly larger than adult males. Total body length at physical maturity varies between ocean basins: 850 cm (females) and 790 cm (males) in the North Pacific Ocean; 850-880 cm (females) and 780-820 cm (males) in the North Atlantic Ocean; and 700 cm (females) and 650 cm (males) in the Southern Ocean. Coloration is also quite variable; populations of the unnamed southern form display the most complex body-color pattern of any species of rorqual. The more general coloration of the Common Minke Whale consists of a bluish dark-gray back and ivorywhite ventral surface, with streaks or lobes of lighter transitional shading, including dark thorax and flank fields and light thorax and flank patches. Dark coloration extends onto lower ...